Determining the proton diffusion coefficient in highly hydrated iridium oxide films by energy dispersive X-ray absorption spectroscopy. (10th March 2023) - Achilli, Elisabetta; Minelli, Simone; Casale, Irene; He, Xiufang; Agostini, Giovanni; Spinolo, Giorgio; Ghigna, Paolo; Minguzzi, Alessandro; Vertova, Alberto
Highlights: Energy Dispersive XAS allows the determination of H + diffusion in oxide-based electrodes. The extrapolated values of D agree with those found by EIS. EIROF presents a H + diffusion coefficient much higher than for other, less hydrous analogous. The high diffusivity of H + in EIROF explains its high real surface area and the high accessibility of its active sites. Abstract: Charge transfer reactions in electrodeposited iridium oxide films (EIROF) are investigated by means of operando energy dispersive X-ray absorption spectroscopy (EDXAS), where oxidation and reduction conditions are selected to drive the Ir(III)/Ir(IV) and Ir(IV)/Ir(V) reactions in acidic solutions. The Ir(III)/Ir(IV) couple is related to a well-known electrochromic phenomenon, while the Ir(IV)/Ir(V) couple might play an important role in the catalysis of the oxygen evolution reactions (OER). In the experiments, current intensity and time-resolved X-ray absorption spectroscopy (XAS) are simultaneously recorded upon application of appropriate potential steps, leading to the independent determination of both the relevant reaction rates and the rate-determining steps. This is allowed by the fast acquisition time (∼10 −2 s) at the ESRF Energy Dispersive XAS (EDXAS) ID24 beam-line, in combination with the highly hydrated amorphous iridium oxide electrode material, which in turn allows to maximize the fraction of Ir sites participating in the electrochemical processes. If the experimental conditions exclude the possibility of having either oxygen evolution (or reduction), the Degree of Reaction (DoR), determined by both electrochemistry and XAS, exhibits exponential time dependence, clearly pointing to diffusion-controlled processes. Vice versa, under concomitant OER + oxidation of iridium centers or ORR + iridium reduction, the electrochemical and XAS DoRs highlight different phenomena, providing fully complementary information of the ongoing electrode reactions. In all cases, data elaboration allows to determine the diffusion coefficient of H + ions within the catalyst layer, that is compared and confirmed by data obtained by electrochemical impedance spectroscopy (EIS). The high values of D obtained for EIROF is compared to values obtained on other IrO2 materials can help in explaining the relevant high electrocatalytic activity.